Persepsi Mahasiswa UIN Walisongo Terhadap Pemilahan Sampah (The Perception of UIN Walisongo Student Toward Waste Segregation) - Milati Azka; Yunita Kurnia Rahman; Fauzan Hidayatullah (Dampak, 2021)
Indonesia is a country with a higher population growth rate and is directly proportional to the waste produced. Likewise, the growth of students of UIN Walisongo Semarang is getting more and more years. Efforts that can be made as a solution to overcome this by selecting waste. This research observes the behavior of students towards waste segregation efforts on campus. Especially waste management by the faculty. This research method uses quantitative analysis research methods, namely in-depth data analysis in the form of numbers. Data collection methods used in the form of a questionnaire using Google form that we spread through social media. Based on the results of the study, the general knowledge of students about waste sorting is largely aware of various types of waste, according to them most need to be organized in terms of waste sorting because of the importance of waste segregation. Most of the students' behavior toward waste sorting has behaved in the form of disposing garbage in its place. The completeness of waste sorting facilities for most of each faculty building does not yet have an adequate trash bin. Students' expectations of waste segregation include the improvement of trash facilities by providing various types of garbage bins supported by the campus Keywords: Perception, Behavior, Waste Sorting, Students ABSTRAK Indonesia adalah negara dengan tingkat pertumbuhan penduduk yang tinggi, yang sebanding dengan jumlah sampah yang dihasilkan. Begitu juga, pertumbuhan jumlah mahasiswa di UIN Walisongo Semarang semakin tahun semakin bertambah. Upaya yang dapat dilakukan sebagai solusi untuk mengatasi hal ini adalah dengan melakukan pemilahan sampah. Penelitian ini mengamati perilaku mahasiswa terhadap upaya pemilahan sampah di kampus, khususnya pengelolaan sampah oleh fakultas. Metode penelitian ini menggunakan metode penelitian analisis kuantitatif, yaitu analisis data mendalam dalam bentuk angka. Metode pengumpulan data yang digunakan berupa kuesioner yang disebarkan melalui Google Form melalui media sosial. Berdasarkan hasil penelitian, pengetahuan umum mahasiswa tentang pemilahan sampah sebagian besar menyadari berbagai jenis sampah, menurut mereka sebagian besar perlu diatur dalam hal pemilahan sampah karena pentingnya pemisahan sampah. Sebagian besar perilaku mahasiswa terhadap pemilahan sampah berupa membuang sampah pada tempatnya. Kelengkapan fasilitas pemilahan sampah untuk sebagian besar gedung fakultas belum memiliki tempat sampah yang memadai. Harapan mahasiswa terkait pemisahan sampah termasuk peningkatan fasilitas tempat sampah dengan menyediakan berbagai jenis tempat sampah yang didukung oleh kampus. Kata Kunci: Perserpsi, perilaku, pemilahan, sampah, mahasiswa